One year of COVID-19 vaccination - Cheng Meng-Li; Zhao Hui; Qin Cheng-Feng (National Science Open)
The year 2021 saw the development and deployment of COVID-19 vaccines at an unprecedented pace, which is a remarkable success in science and technology. COVID-19 vaccines based on different technology platforms have been given to billions of humans globally to minimize the infection and transmission of SARS-CoV-2, and most importantly, to end the COVID-19 pandemic. Here, we provide a snapshot of the current status and future challenge of COVID-19 vaccination after one year.